Ex post evaluation of the regulation: - Montes Tapia, Karina (2024)
This article offers an ex post analysis of the regulatory obligation to include advertising warnings on processed foods, established in the Healthy Food Promotion Law for Children and Adolescents, Law N 30021, more than ten years ago. Through a review of the literature and available information, a retrospective analysis of the regulation is conducted with the purpose of determining whether the involved agents are complying with the established requirements and reacting as expected, and whether all of this is being evaluated by the competent authorities. Key lessons will be extracted for analyzing regulations, the identified information limitations will be discussed, as well as the role of public entities in this context and the limitations of the information identified will be discussed, as well as the role of public entities in this context with a focus on better regulation.